Pengaruh aliran sungai panasen terhadap proses sedimentasi di Danau Tondano - Liany Amelia Hendratta; Arthur Haris Thambas; Lusia Manu; La’la Monica (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
Land use changes and inappropriate land use in the Panasen watershed cause sedimentation in Lake Tondano. The influence of sediment-laden flow on the sedimentation process is still a problem that needs to be studied. The occurrence of flooding in the downstream part of the river due to the process of river silting is a problem that has an impact on economic losses, environmental problems and even unresolved social conflicts. This study aims to obtain the factors causing flooding by evaluating the capacity of the Panasen river cross-section in the downstream part and analyzing the influence of the Panasen River sediment flow on the sedimentation process in Lake Tondano. The study was conducted through field observations in the form of river geometry measurements and sediment flow sampling. Secondary data, namely topographic maps, rainfall data and measured discharge data were obtained from related agencies. Various analyses carried out were hydrological analysis, hydraulic analysis and sedimentation analysis. The hydrological analysis used maximum daily rainfall data obtained from the Noongan rainfall station and measured river discharge from the Noongan River AWLR. The magnitude of flood discharge using the HEC-HMS model with calibrated parameters for various return periods of 2, 5, 10, 25, 50 and 100 years were obtained at 50.2 m3/sec, 71.6 m3/sec, 82.1 m3/sec, 91.8 m3/sec, 97.2 m3/sec and 101.4 m3/sec. From the hydraulic analysis, it was obtained that under Q100 and lake tides, all river segments were unable to accommodate flood discharge. The flood water level (overflow) was at 1.2 - 3.1 meters and tended to occur towards the right river bank. The amount of sediment transport was determined after obtaining the dissolved sediment content, which was 6.16 gr/m3, resulted in an average increase in sediment volume to the lake for 30 years of 3,215,104.7 m³ or a thickness of 72.15 mm. The results of the study showed that the amount of sediment entering the lake was quite large, so that management efforts were needed in the Panasen River watershed, namely in the form of land conservation measures and determining appropriate land use.